Reinterpretación del pasado fotográfico de la Misión Josefina con la Asociación de Mujeres Parteras Kichwas del Alto Napo (AMUPAKIN) - Saúl Uribe Taborda; Patricia Bermúdez Arboleda; Alexandra Ángel Penagos (Revista de Estudios Sociales, 2020)
In 2015, a corpus of 70 photographs registered between 1922 and 1932 by the Josephites of Murialdo was found in the Ecuadorian Library Aurelio Espinosa Polit (BEAEP), in the city of Quito. From the analysis of this corpus, a proposal was made to understand the configuration of the processes of visual representation and subjectivation of the Napo Runa Amazon Indians framed in that historical past, as well as in the ethnographic present. The article proposes two objectives: the first, to analyze the historical context of production of the photographic corpus. And the second, to investigate how the processes of visual representation and subjectivation are currently reinterpreted by the Association of Kichwa Midwives of the Upper Napo (AMUPAKIN).